Social relations and health in an ethnically diverse social housing area selected for large structural changes compared to municipal levels: a Danish survey study - Monica F. Kvorning; Siv S. Nygaard; Abirami Srivarathan; Cathrine J. Lau; Rikke Lund (BMC, 2023)
Abstract Background This study aims to describe demographics, social relations and health in an ethnically diverse social housing area selected to undergo large structural changes and compare it to the surrounding municipality. Furthermore, to explore the association between social relations and self-rated health (SRH) and the interaction with country of origin in both populations. Methods Data sources include a multilingual interviewer-driven survey study in a social housing area (N = 209) and a municipal health survey (N = 1,638) among residents aged 45 + years. Information on social relations include contact frequency with and support from family, friends, and neighbors. Descriptive and multivariate logistic regression analyses adjusted for age, sex, and country of origin are presented, as well as joint effect analyses of social relations and country of origin on SRH. Results In the social housing area, 38.8% of the respondents reported poor SRH compared to 19.5% in the municipality. In both study populations low contact frequency was associated with poor SRH, however insignificantly in the social housing area compared to the municipality sample, OR = 1.50 (0.65-3.46) vs. OR = 2.42 (1.70-3.45). Joint exposure to having non-Western background and low contact frequency was strongly associated with poor SRH in the social housing area, OR = 6.28 (1.80-21.89) but less so in the municipality, OR = 3.67 (1.55-8.69). The same tendency was seen regarding low support from social relations. Conclusions This study provides insight to a population that is generally underrepresented in survey studies. In the social housing area, approximately twice as many reported poor SRH compared to the municipality data. In both populations, low contact frequency and low support were associated with poor SRH. Residents with weak social relations and non-Western origin simultaneously were more likely to report poor SRH in the social housing area specifically but less so in the municipality, indicating a higher vulnerability among the residents in the social housing area.